If Nothing is Achieved: Who Pays for the Brexit? - Michael Hüther; Matthias Diermeier; Markos Jung; Andrew Bassilakis (Intereconomics, 2018)
The United Kingdom will depart from the European Union in March 2019. Numerous open questions remain about details and conditions especially with regard to post-Brexit EU-UK trade relations. In case of a negotiation failure, a 'hard Brexit' could cause considerably high costs on both sides of the Channel. In the short run, companies will be charged more than 15 billion euro as tariffs. In the long run, UK-EU trade could be reduced up to 50 percent.
Keywords: 330; Brexit; European governance; Tariffs; Trade policy; WTO